The area radiation gamma and neutron origin telemetry system - Hutchins, Robyn M. (Kansas State University, 2023)
In today’s global security enviroment, the opportunities to alert to, search for, and identify radioactive material have increased as both China and Russia grow their nuclear stockpiles and aggressive posture, unrest in the middle east continues, and US borders endure an influx of migrants. Traditional mobile radiation detector systems are equipped with He-3 gas detectors that are often bulky, expensive, and offer limited information to the user. The need for low-cost, high-efficiency, mobile detection systems sensitive to thermal neutrons and gamma rays persists. Single-sided MSNDs were developed as an early compact, low-power, inexpensive, mass-producible, and rugged solution offering moderate intrinsic thermal-neutron detection efficiency (~30%). While the single-sided MSNDs could be stacked to increase the neutron detection efficiency to up to 42%, aligning the devices was unreliable. Dual Sided MSNDs were then developed and coupled with superior LiF backfill densities and increased trench depth etching processes on 1.5-mm thick silicon wafers, to achieve record-breaking intrinsic thermal-neutron detection efficiencies of 69.3 ± 1.5 %. In the present work, an alternative doping scheme known as the pvp-n-dot for DS-MSNDs was implemented. The pvp-n dot doping profile was designed to bias across the p-type doped trenches and an n-type doped ring on the perimeter of the trenches. The top side of the device is read out through the traditional center bond pad, while the back side of the device is read out through the bottom contact. The devices produced with the pvp-n-dot doping scheme achieved an intrinsic thermal neutron detection efficiency of 64% ± 2.5% and on average, achieved an intrinsic thermal neutron detection efficiency of approximately 24%. The GRR was determined to be 5.69E-05 at a gamma-ray dose rate of 10mR/hr. To accompany the thermal neutron detectors in the mobile radiation detection system known as the ARGANOT (Area Radiation Gamma and Neutron Origin Telemetry), SrI₂(Eu) and later CsI(Tl) scintillator using SiPMs were used to alert to gamma-rays and supply the user with gamma-ray spectrums. To ensure good energy resolution of the spectrum regardless of environmental conditions, a temperature-correcting algorithm was implemented for each module to maintain the energy calibration. Using Gamma-ray Detector Response and Analysis Software (GADRAS), directionality, source identification, and activity estimation were implemented. The ARGANOT underwent extensive testing as a single module and as a full system worn in a garment on and off a phantom body. Results indicate that the ARGANOT optimal performance is best achieved when worn by a user, but it can alert to sources when operating in a standalone configuration or when flown on an Unmanned Aerial Vehicle. The cost-effective ARGANOT system presents many benefits to a user such as its high efficiency, low profile, and discrete appearance; the ability to operate as a stand-alone module in a passive monitoring situation or as a directionality capable vest; and the ability to instantly provide the user information about the environment through tools such as GADRAS.
Keywords: Radiation detection; Mobile radiation detection; Radiation spectroscopy; Neutron detections